HADIS TENTANG NIKAH MUT‘AH (KAWIN KONTRAK) - Dakhirotul Ilmiyah (LP2M Universitas Ibrahimy, 2017)
This research talks about contract marriage or in Islam known as mut'ah marriage. The marriage of a contract is a marriage which is done according to the time specified. When time is up then man can leave the woman. According by Ammianus Mercellinus, such marriages were practiced by Arabs around the 4th century AD. This news needs to be clarified because existence of women abandoned by men is probably not in terms of marriage but they only help mas to prepare in war. In Islam, once allowed to marry contract because Sahabat have not long left period of ignorance and infidelity. It is allowed under conditions in an emergency such as it is permissible for eating pork. Even many narrations that tell about mut'ah marriage and made sub in the book of al-sittah. Ibn Hajar explain the history of al-Bukhari, that contract marriage was ever allowed, then banned in the end. Sayyidina Ali RA, at the end of his story he was commented that allow of contract marriage was removed. The permissibility of mut'ah marriage in the pre-war khaibar era was then banned in the khaibar war. Allowed again when the conquest of Mecca when the war aut’as forbidden forever. Law of mut'ah marriage is forbidden those who do marriage mut'ah or al-nikah al-Muaqqat become void. Allow of mut'ah marriage in Islam only in war time emergency as described above. Imam mazhahib arbi'ah agree that mut'ah marriage is equal to al-nikah al-muaqqat. Besides, they also agree whether the agreement is openly or hidden remain void. Besides to the nass that is history sahih of the Prophet SAW, the marriage of the contract does not match purpose of marriage.